Offshoring language-sensitive services: a case study. (12th October 2018) - Bjørge, Anne Kari; Whittaker, Sunniva
Abstract : Purpose: The purpose of this paper is to focus on corporate communication issues that arise when a company offshores language-sensitive services to a country which does not have a workforce with the required language skills. It explores the consequences of adopting a total immersion policy and annual testing regime to build and maintain linguistic competence among the workforce, with regard to motivation, challenges and coping strategies. Design/methodology/approach: The approach adopted was semi-structured interviews with management and employee representatives, interviewed separately. The interviews were transcribed and submitted to content analysis, supported by relevant company information. Findings: The company's language policy has generated a user environment where language proficiency is developed in corporate interaction, and where the workforce is motivated by both intrinsic and extrinsic factors. Strategic decisions relating to language policy need to take the workforce's input into account to discuss the testing regime with a view to test content and relevance. Research limitations/implications: The findings relate to a limited material of 6 interviews with 14 interviewees in total. Practical implications: The paper focusses on how to strike a balance between developing the skills needed to perform job tasks and preparing for new more complex tasks without demotivating the workforce. The conclusion sets out managerial implications. Social implications: The paper contributes to understanding the dynamics of working in a multilingual context. Originality/value: To the authors' knowledge the specificities of offshoring of language-sensitive services with regard to motivation and coping strategies have not been explored previously. The fact that the services in question have to be carried out in a minor language and that a total immersion strategy has been adopted also represents something new.